Determinación de la fragmentación del bosque seco del arroyo Pechelín, Montes de María, Caribe, Colombia (2015)
The present work characterized the current fragmentation of the relictual tropical forest dry of the Pechelín stream drainge, in Montes de María, Colombian Caribbean. The selection and calculation of cover and size of the forest fragments was done using satellite images and geographical information systems. The degree of fragmentation, spatial continuity and Patton form diversity index were calculated. The average area of the patches was 16.08 ha (Max. 149.8 ha and Min. 0.17 ha). The perimeter average was 2979.99 m2 (Max. 12475.76 m2 and Min. 4334.98 m2). The average patch size is small so that probably affects the ecological stability of the study area due to microclimate changes. The obtained data show that fragmentation exists in the forest of the study area. According to the degree of fragmentation index (F = 0.355), the forest area is in the insular category, with a continuity index of 3.98, or discontinuous. As for shape, the most common was irregular (41.7%), followed by oval-oblong (19.4%). Conditions of remaining forest fragments are unfavorable with the high degree of fragmentation caused by local agricultural practices.